Analisis Fitokimia Berbasis GC-MS dan Evaluasi Aktivitas Antioksidan Metode DPPH dari Ekstrak Etanol dan N-Heksan Daun Bidara (Ziziphus mauritiana Lam.) - Maharani Zahra; Rahma Yulia; Syarifah Nadia; Bunga Rimta Barus (Journal of Pharmaceutical and Sciences, 2026)
Background: The increasing public interest in herbal medicine which is safer and rarely causes side effects has made people use more natural ingredients as a source of bioactive compounds. One promising plant is the bidara leaf (Ziziphus mauritiana Lam.), known for its rich supply of secondary metabolites, including alkaloids, flavonoids, glycosides, and terpenoids, which boast pharmacological benefits, especially in their role as antioxidants. Objective: This research is conducted to determine the phytochemical compounds and examine the antioxidant potential of bidara leaf extracts prepared with ethanol and n-hexane, using experimental method. Methods: The extraction was done through maceration using 96% ethanol and n-hexane as solvents, and then we analyzed the phytochemicals via phytochemical screening and GC-MS. For checking antioxidant activity, we used the DPPH method, which involved figuring out the maximum wavelength, the operating time, measuring absorbance, and calculating the IC50 value. Results: From the phytochemical analysis, it turned out that ethanol extracts of bidara leaves feature a richer array of bioactive compounds, including alkaloids, flavonoids, glycosides, and terpenoids or steroids, in contrast to the n-hexane extracts, which only include alkaloids, glycosides, and terpenoids or steroids. Analysis using GC-MS identified that the ethanol extract was dominated by fatty acid ester compounds, including methyl palmitate and methyl oleate, while the n-hexane extract contained non-polar compounds such as squalene and tetratetracontane. Through the DPPH approach, the antioxidant activity of ethanol and n-hexane extracts was demonstrated by IC₅₀ values of 4.488 µg/mL and 7.54 µg/mL, respectively, both of which are classified as very strong, although still lower than vitamin C, which has an IC₅₀ of 2.47 µg/mL. Conclusion: The analysis indicates that the ethanol extract exhibits stronger antioxidant activity compared to the n-hexane extract.